2019
DOI: 10.1111/tbed.13281
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory disease due to mixed viral infections in poultry flocks in Egypt between 2017 and 2018: Upsurge of highly pathogenic avian influenza virus subtype H5N8 since 2018

Abstract: For several years, poultry production in Egypt has been suffering from co-circulation of multiple respiratory viruses including highly pathogenic avian influenza virus (HPAIV) H5N1 (clade 2.2.1.2) and low pathogenic H9N2 (clade G1-B). Incursion of HPAIV H5N8 (clade 2.3.4.4b) to Egypt in November 2016 via wild birds followed by spread into commercial poultry flocks further complicated the situation. Current analyses focussed on 39 poultry farms suffering from respiratory manifestation and high mortality in six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 78 publications
6
41
0
Order By: Relevance
“…H5N8: Phylogenetic analysis of the full HA gene of the four H5N8 viruses indicated that they clustered together within clade 2.3.4.4 group B (Figure 1) with recently isolated Egyptian H5N8 strains from domestic birds. Sample 2 clustered with 2018 strains with the characteristic amino acid substitution 175L previously reported in recent Egyptian samples [21]. All four samples possessed multibasic cleavage sites in the motif PLREKRRKR/GLF and six potential glycosylation sites at positions 10, 23, 165, 286, 483, and 542 (H5 numbering).…”
Section: Prevalence and Genetic Characterization Of Influenza A Virusesmentioning
confidence: 53%
“…H5N8: Phylogenetic analysis of the full HA gene of the four H5N8 viruses indicated that they clustered together within clade 2.3.4.4 group B (Figure 1) with recently isolated Egyptian H5N8 strains from domestic birds. Sample 2 clustered with 2018 strains with the characteristic amino acid substitution 175L previously reported in recent Egyptian samples [21]. All four samples possessed multibasic cleavage sites in the motif PLREKRRKR/GLF and six potential glycosylation sites at positions 10, 23, 165, 286, 483, and 542 (H5 numbering).…”
Section: Prevalence and Genetic Characterization Of Influenza A Virusesmentioning
confidence: 53%
“…Cocirculation of HPAI (H5N1, H5N8) and LPAI (H9N2) viruses in poultry provides an opportunity for reassortment. Co-infection of birds with A(H5) and A(H9N2) viruses in Egypt is not uncommon, yet few reassortments have been detected to date (Abdelwhab el et al 2010;Kayali et al 2016;Hassan et al 2019). A(H5N1)/ A(H9N2) reassortants have been detected in other countries where these viruses cocirculate, suggesting that there is not complete incompatibility between their gene segments (Monne et al 2013;Marinova-Petkova et al 2016).…”
Section: Reassortment Of Hpaiv H5nx In Egyptmentioning
confidence: 99%
“…Despite their classification as LPAIV, they are associated with severe disease in poultry leading to significant economic losses [15,16]. It has been suggested that the strikingly distinct clinical signs induced in experimental and natural H9N2 infections are due to opportunistic viral and bacterial co-infections with H9N2 acting in synergy as an immunosuppressive agent [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%